Increasing learning focus for attention deficit hyperactivity disorder (ADHD) children; photography as an alternative method / Meor Hasmadi Meor Hamzah … [et al.] - Meor Hamzah, Meor Hasmadi; Baharuddin, Nor Fariza; Mohd Herrow, Mohd Firdaus; Abdul Samat, Raziq; Shaari, Sharifah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This research is about how photograph image as a medium in increasing learning focus for ADHD children in Hospital Permai Tampoi Johor, as it is the government main center for ADHD treatment especially focuses on kids in south Malaysia that gain education and therapist. Through several observations and data collection about ADHD children are collected, the prototype were test to the ADHD children with help from the experts such as the teacher and the senior nurse. These kinds of research are very useful for improving the level of learning and focus to the ADHD children. The objective is to explore the usage of photograph as an alternative method in learning for ADHD children in Hospital Permai Tampoi Johor. The process of learning of ADHD children is quite challenging because they are lack of focus. The method that used as interview, giving questionnaires to children based on the interview data, results from the interview will produce the prototype design and test to the ADHD children and the results from the test will be the findings of this study.